Knowledge, attitude and perception of final year pharmacy students at Kulliyyah (faculty) of Pharmacy IIUM on pharmacogenomics - Zulkifli, Nurul Hamizah; Ahmad Jahari, Zahriyatul Ain; Zaman, Zaizal Khalidah; Abdul Basir, Nurul Azzwa; Masazlan, Siti Nadhirah; Mohamed Nazar, Nor Ilyani (2019)
Introduction: Pharmacogenomics is a science that incorporates three different field of studies; pharmacology, medicine and genomics. It has been found out that, applying pharmacogenomics in clinical setting can help in improving patient outcome hence justifying the needs for this subject to be incorporated in the curriculum of a pharmacy program. Objectives: This study aimed to evaluate the knowledge, attitude and perception regarding pharmacogenomics among final year pharmacy students. Methodology: In this cross-sectional study, the respondents were given a set of validated questionnaires each, which consists of demographics, knowledge, attitude and perceptions domains. All final year students were recruited. Results: Out of 94 participants, only 73.4% had completed the survey. Based on the results of the survey, only about 26.1% respondents have high level of knowledge whereas 46.4% and 27.5% of the participants have medium and low level of knowledge respectively. It was observed that 63.8% students have positive attitude towards pharmacogenomics while 7.2% having negative attitude and the rest are intermediate. In addition, majority of the students have good perception on pharmacogenomics with 59.4% responses, followed by 37.7% for medium perception and only 2.9% have bad perception toward pharmacogenomics. Conclusion: The results showed low knowledge of the students on pharmacogenomics subject but with positive attitude and good perception towards enhancement of this field of study in the curriculum.